Counterconditioning as Treatment to Reduce Nocebo Effects in Persistent Physical Symptoms: Treatment Protocol and Study Design - Meijer, Simone; van Middendorp, Henriët; Peerdeman, Kaya J.; Evers, Andrea W. M. (Frontiers in Psychology, 2022)
Persistent physical symptoms have a high prevalence and a large impact for patients and society. To date, treatment effects for these symptoms are often limited. Nocebo effects (i.e., negative outcomes that are not attributable to active treatment components) have a substantial influence on treatment success and can be established via learning through classical conditioning. Therefore, interventions aimed at reducing nocebo effects by means of counterconditioning, in which an alternative association (inhibiting the previous association) is learned, could be a promising method for improving physical symptoms. In experimental studies, counterconditioning has been shown promising in reducing experimentally-induced nocebo effects on pain and itch. Application of counterconditioning procedures to reduce nocebo effects on clinical symptoms has yet to be researched. This paper provides a protocol of a 6-week counterconditioning intervention aimed at reducing nocebo effects and clinical pain in patients with fibromyalgia. A study in patients with fibromyalgia is proposed to examine the feasibility and potential effectiveness of this counterconditioning intervention as a novel treatment method for reducing nocebo effects and generalization to clinical pain symptoms. Results can help design an optimized treatment protocol for reducing nocebo effects, based on the experiences of participants and the first indications of treatment efficacy.